Xq28 Duplications and Epilepsy: Influence of the Combinatory Duplication of MECP2 and GDI1 - Yamamoto, Toshiyuki; Shimada, Shino; Shimojima, Keiko; Eto, Kaoru; Yoshitomi, Shinsaku; Yanagihara, Keiko; Imai, Katsumi; Oguni, Hirokazu; Okamoto, Nobuhiko (Journal of Pediatric Epilepsy, 2015)
Xq28 duplications including the MECP2 (Methyl-CpG-binding protein 2) cause an X-linked recessive neurodegenerative disorder that presents symptoms such as early developmental delay, progressive deterioration, and intractable epilepsy. Submicroscopic interstitial duplication in the MECP2 region is one of the most frequently observed submicroscopic chromosomal aberrations in patients with intellectual disability. This high prevalence is derived from the genomic instability characteristic of this region due to segmental duplications that are densely located in this region, which are prone to cause nonallelic homologous recombination during meiosis. Patients with MECP2 duplications generally begin to show epilepsy after 6 years of age. Therefore, incidence of epilepsy is high in adolescents. Although many types of seizures have been reported in patients, the most frequently observed seizure types were absence seizure and generalized tonic–clonic seizures. Because drop attacks are frequently seen, such epileptic attacks are sometimes life-threatening. We encountered a patient who showed epileptic spasms during infancy with a relatively larger duplication that encompasses MECP2 and GDI1 (GDP dissociation inhibitor-1). This led us to speculate that the combinatory duplication that includes MECP2 and GDI1 may cause severe epileptic features; however, most of the previously reported patients with combined duplications of MECP2 and GDI1 did not showed early occurrence of epilepsy. Therefore, further information would be required to confirm if the combinatory duplication of MECP2 and GDI1 exerts any influence on the severity of epilepsy.
Keywords: Xq28 duplication; epilepsy; intellectual disability; MECP2; GDI1